Linguistic Ideologies About American Indigenous Languages: A Systematic Review of Research Articles - Cisternas Irarrázabal, César; Olate Vinet, Aldo (Íkala, Revista de Lenguaje y Cultura, 2020)
The comprehension of language ideologies is essential for describing the processes of conservation and displacement of minority languages. This work carries out a systematic review of the publications on language ideologies about American indigenous languages that are indexed in Web of Science. It has as its main purpose to describe the research lines, methodological orientations, theoretical frameworks, typologies, and the most relevant conclusions that those investigations provide to this field. The review considered articles published between 1980 and 2016, and produced 25 articles. Results show the prevalence of a methodological frame that is exclusively qualitative, while in the conceptual plane, a vast taxonomy of ideologies, which includes several denominations for the same ideological frame, is observed. They also reveal the relevance of language ideologies in processes such as identity construction, language revitalization, language planning, language valuation, cultural and identitary resistance, among other sociolinguistic and sociocultural processes.